Access to a variety of Ge(II) and Sn(II) compounds through substitution of hypersilyl moiety - Bisai, Milan Kumar; Ajithkumar, V. S.; Gonnade, Rajesh G.; Sen, Sakya S. (Organometallics, 2021)
We have prepared amidinato-germylene (3) and -stannylene (4) with a tris(trimethylsilyl)silyl substituent and subsequently substituted the hypersilyl moiety by reacting 3 with chlorophosphines, which led to phosphino germylenes (5 and 6) with concomitant liberation of (Me3Si)(3)SiCl. Exploiting the fluoride affinity of the silicon atom, we have prepared pentafluoropyridyl germylene (7) and -stannylene (8) by reacting 3 and 4 with C5F5N with simultaneous elimination of (Me3Si)(3)SiF. These are the first examples of aryl germylenes or stannylenes prepared via C-F bond activation of a perfluoroarene. The reaction of 4 with Me3NO resulted in a novel Sn2O2 ring (9). All compounds were characterized by single-crystal X-ray structure determination studies.

Activation of carbon disulfide by a hypersilyl germylene - Ajithkumar, V. S.; Khilari, Nripen; Ghanwat, Pratiksha B.; Venugopal, Geethu; Koley, Debasis; Sen, Sakya S. (Dalton Transactions, 2024)
In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C( 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 S)-S-Si(SiMe3)3 (2). Interestingly, the addition of NHC to 2 allows the release of NHCCS2 with concomitant regeneration of 1. Addition of another equivalent of 1 or an analogous hypersilyl silylene, [PhC(NtBu)2Si-Si(SiMe3)3], to 2 led to the formation of compounds with a GeS (3) or a SiS (4) bond. In this work, the insertion of CS2 into the Ge-Si bond of PhC(NtBu)2Ge-Si(SiMe3)3 (1) has been investigated, resulting in the formation of PhC(NtBu)2Ge-C(S)-S-Si(SiMe3)3 (2).